PENINGKATAN MARKETPLACE ONLINE SEBAGAI STRATEGI PENINGKATAN PENDAPATAN PELAKU USAHA MIKRO - Azy Athoillah Yazid; Lelo Sintani; Dimas Puji Santosa; Al-Amin (Adiba Aisha Amira, 2025)
The purpose of this research is to see how Increasing Online Marketplace as a Strategy to Increase Income for Micro Business Actors. The method of this research is This research is a type of literature research; This means that the information materials used come from library sources in the form of books, encyclopedias, magazines, journals, newspapers, journals, and others. The form of this research is descriptive, analytical, and critical. Therefore, the author can comprehensively describe how Local Marketplace Development is a Strategy for Increasing Income of MSME Actors. The results of this research are Good business education and financial management are essential to strengthen micro businesses in the long term. The key to success for micro businesses lies in adapting to market changes, product innovation, and efficient management, while maintaining customer satisfaction.